РОМАН ЖАНРИНИНГ КУЛЬТУРОЛОГИК ҚИЁФАСИ (Scientific journal of the Fergana State University, 2023)
In the article the genre of the novel in culturological aspect is considered. By comparative analysis the Kyrgyz writer of the XX th century Chingiz Aitmatov’s novel “Jamila” and modern Uzbek writer Lukhmon Burikhon “Men in heat”, the peculiarities of the themes and ideas of the two novel are revealed.